2020
DOI: 10.3389/fneur.2020.593490
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight on the Role of the Cerebellum for Executive Functions and Emotion Processing in Adults

Abstract: Objective: We investigated whether the cerebellum plays a critical or supportive role in in executive and emotion processes in adults. Many investigators now espouse the hypothesis that participants with cerebellar lesions experience executive functions and emotions (EE) disorders. But we hypothesized that these disorders would be milder if the damage is relatively limited to the cerebellum compared to damage involving the cerebellum plus additional cortical areas.Methods: We studied veterans with penetrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…First, the brain-behavior relationship in SCA3 has not been comprehensively evaluated using MRI-based brain networks. We postulate that a distributed network, rather than an individual brain region such as the cerebellum, is responsible for the clinical syndrome in SCA3 (Beuriat et al, 2020;Spampinato et al, 2020). In support, the 3D-FD analysis showed that SCA3 neuropathology involves dissociation in the cerebellar-cerebral network (Huang et al, 2017;Jao et al, 2019b).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…First, the brain-behavior relationship in SCA3 has not been comprehensively evaluated using MRI-based brain networks. We postulate that a distributed network, rather than an individual brain region such as the cerebellum, is responsible for the clinical syndrome in SCA3 (Beuriat et al, 2020;Spampinato et al, 2020). In support, the 3D-FD analysis showed that SCA3 neuropathology involves dissociation in the cerebellar-cerebral network (Huang et al, 2017;Jao et al, 2019b).…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, disruption in the cerebellar-cerebral network and prefrontal-striatal circuit were involved in the cognitive impairment in SCA3 (Lindsay and Storey, 2017). In this case, the cerebellum serves as a hub in the network that prepares for neural processing to optimize the action sequencing on the EF task (Beuriat et al, 2020). Cerebellar degeneration compounds the EF impairment due to the frontal lobe atrophy in SCA3 patients (Klinke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach changed in the 1980s when research demonstrated that patients with cerebellar damage exhibited cognitive deficits (Schmahmann, 1991). Recently, much evidence has shown that the cerebellum affects not only visuospatial and verbal function, and declarative memory but also more complex behavior regulation processes, namely EF (Mak et al, 2016;Myers et al, 2017;Beuriat et al, 2020). A study found that patients with cerebellar infarction exhibited impaired cognitive function and had reduced fALFF values in the cerebellum compared to HC (Fan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that Cognitive but not affective ToM deficit was also related to working memory performance 64 . Our group has shown that the role of the cerebellum in executive function is supportive since it appears to primarily compute the motor component of working memory 47 . Also, in patients with cervical dystonia, it was reported that only cognitive ToM was impaired in those with tremor compared to those without motor impairment 65 .…”
Section: Discussionmentioning
confidence: 92%
“…Neuroimaging assessment and image pre-processing were done using the same method described elsewhere 47 . Detail of the axial computed tomography (CT) acquisition is described in the e-methods.…”
Section: Methodsmentioning
confidence: 99%